Determination of Formation Time of Calcareous Cements in Marine Sandstone and Their Influence on Hydrocarbon Accumulation: A Case Study of the Carboniferous Donghe Sandstone in the Hadexun Oilfield, Tarim Basin. (10th March 2021) - Cui, Jingwei; Liu, Yongfu
Abstract : Based on core observations, the microheterogeneity, diagenetic features, diagenetic mineral compositions, and stable isotopes of cements in the calcareous interlayers in the Donghe sandstone were studied by polarizing microscopy, cathodoluminescence microscopy, X-ray diffractometry, isotope ratio mass spectrometry, and other techniques. By determining the proportions of cements of two phases by a statistical method and their clumped isotope values by an end-member method, the multiphase calcareous cementation was shown to be the major contributor to densification. Cluster isotopes revealed that the average formation temperatures of calcareous cements in phases II and III of cementation were 45–50°C and 80–90°C, indicating that they were products of the A and B phases during early diagenesis, respectively. According to the homogenization temperatures of coeval salt-water inclusions associated with hydrocarbon inclusions, which range from 100°C to 130°C, basin modeling revealed that the basin underwent mainly one stage of hydrocarbon charging during 8–5 Ma in the Miocene period. The cements of the two phases in the oil-free calcareous interlayers in the Donghe sandstone, which are the main controlling factor of the oil-water distribution in the reservoir at present, formed much earlier than the oil filling in the oil-bearing sandstone.